Respuesta :

Answer:

The answer is -1 - 4x = y

Step-by-step explanation:

We have three points to check each equation

(-1 , 3) , (0 , -1) , (1 , -5)

The point (0 , -1) is the point of y-intercept, so we have only two equations have y-intercept = -1

* -1 + 4x = y  and -1 - 4x = y

Now we will check both

-1 + 4(-1) = -1 + -4 = -5 not 3 then its wrong equation

-1 - 4(-1) = -1 + 4 = 3⇒ (-1 , 3)

-1 - 4(0) = -1⇒ (0 , -1)

-1 - 4(1) = -1 - 4 = -5⇒ (1 , -5)

So the equation -1 - 4x = y satisfied the three pairs

ACCESS MORE